Securitization - A critical assessment in the light of the financial crisis - Marinova, Milena; Krupová, Lenka, 1964-; Marek, Petr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2009)
My dissertation thesis provides a comprehensive analysis of the principles of securitization techniques, of their attendant shortcomings, their regulatory treatment and the recent proposals for reducing complexity in accounting standards with relevance for securitizations. The explosion of securitization and related innovative credit risk transfer products largely expanded the magnitude and diversity of issuers, investors and securities. With this expansion numerous market participants began to wrongly believe that risk was not only shared more widely, but also that it disappeared from the system altogether. The application, or to be more precise, the misapplication of securitization in the mortgage market had fatal consequences for the financial sector worldwide. Before securitization, sub-prime mortgage lenders retained the loans that they originated on their balance sheets and therefore cared about their credit quality. Securitization techniques and related innovative financial instruments enabled the export of sub-prime mortgage structural problems from the United States globe-wide via the financial intermediaries. More over, securitization techniques and related credit risk transfer products enabled single banks to reduce their individual risk while at the same time transferred new and greater risks to the financial system. Meanwhile a lot was written on the causes for the recent financial crisis. In most cases inadequate ratings provided by the credit rating agencies and different principal agent problems were addressed. I present both for completeness in my work. However, I argue that not only the credit rating agencies are to blame for the inadequate reflection of securitization and related financial innovations and subsequently for the financial turmoil. The international and national financial supervisors in fact supported the credit rating agencies to further establish their businesses.
What turned obvious during and after the financial turmoil started mid-2007 is that financial regulation failed to reach its main goal - ensuring stability of the financial system. It failed despite of the "regulatory achievements within Basel II" elaborated over the past ten years. In particular, securitization and related credit risk transfer products were not adequately treated in Basel II. Securitization-related products such as Credit Derivatives on Securitization Underlyings and numerous other complex financial innovations, as presented in my thesis, were not even thought of in Basel II. In fact, Basel II turned to do little to make the financial system more resilient. The need for further revisions in banking regulation is currently more than obvious. Furthermore, it is time to ask if the developments in Basel II are the right way to address the current risks within the financial system and hence if Basel II is the right way of banking regulation and supervision altogether. With the development of both Basel Accords (Basel I and Basel II) capital ratios became the center of banking regulation. However, capital ratios are obviously not sufficient as a measure for a systemic financial stability. These questions arise at least when financial stability and soundness are still the intended objectives and believed to be ensured through Basel II. My merits in this dissertation work root in the multi-facet analysis of securitization techniques that I provide. Up to date a comparable analysis of securitization techniques which addresses the wide spectrum of securitizations' issues - such as (i) their treatment and the related attendant flaws within the regulatory framework Basel II, (ii) the various microeconomic deficiencies related to securitizations, and (iii) the implicit macroeconomic threads of exporting credit risk and de-balancing financial stability through securitization techniques - has not been provided in the comprehensive way I built up my analysis. A
Vedoucí práce: Lenka Krupová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2010
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2010
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor disert. práce]; disertace; dissertations